Partisipasi Masyarakat dalam Mewujudkan Kuningan sebagai Kabupaten Konservasi (Studi di Kabupaten Kuningan) - Suwari Akhmaddhian; Anthon Fathanudien (UNIFIKASI : Jurnal Ilmu Hukum, 2015)
Public Participation in realizing Kuningan as a research location Conservation District is performed in Kuningan District. The purpose of this study was to determine the Implementation Regulations Kuningan District No. 12 of 2007 on the Conservation of Water Resources. and to find out what people's participation in realizing Kuningan as Conservation District. This research can be useful, among others, the study has been practically is can be used in policy-making related to the environment and settings to improve community participation in supporting the preservation of the environment and conservation, especially in the District Kuningan and generally in Indonesia. The method used by the researchers in this study is a discussion of evaluative method of analysis, which is a method of collecting and presenting data obtained to analyze the actual situation and then performed a rational analysis based reference juridical through library research and field research. The results of research that community participation in realizing the Kuningan as a conservation district is a step forward because it participates in government programs to help the protection and preservation of the environment that will create a beautiful and healthy environment. Forms of community participation brass districts namely through bridal care environment (pepeling), students are concerned about the environment (seruling) and officials concerned.about.the.environment (apel). Keywords: Participation, Community, Conservation, Environment